Innovations in Intelligent Machines -3 Contemporary Achievements in Intelligent Systems - Jordanov, Ivan.; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book aims to promote a sample of current theoretical and application oriented intelligent systems research specifically in the field of neural networks computing. It presents examples of experimental and real-world investigations that demonstrate contemporary achievements and advances in the area of intelligent systems.   This book will prove as a valuable source of up-to-date theoretical and application oriented research in intelligent systems for researchers and postgraduate students.  .
From the Contents: An introduction to Contemporary Achievements in Intelligent Systems -- Market Power Assessment Using Hybrid Fuzzy Neural Network -- Coaching Robots: Online Behavior Learning from Human Subjective Feedback -- Persian Vowel Recognition Using the Combination of Haar Wavelet and Neural Network -- The Reproduction of the Physiological Behaviour of The Axon of Nervous Cells by means of Finite Element Models -- A Study of a Single Multiplicative Neuron (SMN) Model for Software Reliability Prediction -- Numerical Treatment for Painlevé Equation I using Neural Networks and Stochastic Solvers.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence